CHILDREN’S NUTRITIONAL STATUS AND THEIR PARENTS’ FEEDING PRACTICES, SHOPPING MOTIVATION, AND STRESS AT MEALTIME DURING THE PANDEMIC COVID-19 - Kamarjan, Athierah; Jaafar, Nurul Hazirah (International Journal of Allied Health Sciences, 2022)
Introduction: The COVID-19 pandemic has affected a variety of demographic groups, from infants to the elderly, particularly in their psychosocial, economic, and educational systems. This study examined the nutritional status of children and their parents’ feeding practices, shopping motivation, and mealtime stress during the COVID-19 pandemic. Methods: A hundred-five caregivers and their children were recruited via social media. The information on feeding practices, shopping motivation, and mealtime stress was requested of caregivers via a Google form, along with information on the anthropometric measurements and dietary intake of their children. Qualitative data on dietary intake and feeding practice changes were collected. Data were analyzed using descriptive analysis, and qualitative data were analyzed using thematic analysis. Results: There are big concerns about the children’s food intake and body weight as it is beyond the normal requirement for their age. As for parental feeding behaviour, the results indicated that parents have acceptable practices, high consideration when shopping but most of them (55%) experience stress at mealtime during the COVID-19 pandemic. Conclusion: In conclusion, this study provides insight into children’s nutritional status as well as positive and negative parental behaviour during the COVID-19 pandemic which could be explored further in future studies whereby necessary intervention is deemed needed.